Evaluation and Management of Neurogenic Thoracic Outlet Syndrome with an Overview of Surgical Approaches: A Comprehensive Review - Lim C (Journal of Pain Research, 2021)
Christine Lim,1 Yasaman Kavousi,2 Ying Wei Lum,2 Paul J Christo1 1Division of Pain Medicine, Department of Anesthesiology and Critical Care Medicine, The Johns Hopkins University School of Medicine, Baltimore, MD, USA; 2Division of Vascular Surgery and Endovascular Therapy, The Johns Hopkins University School of Medicine, Baltimore, MD, USACorrespondence: Paul J Christo Email pchristo@jhmi.eduAbstract: Neurogenic thoracic outlet syndrome (NTOS) represents a disorder believed to involve compression of one or more neurovascular elements as they exit the thoracic outlet. This comprehensive literature review will focus on the occurrence, classification, etiology, clinical presentation, diagnostic measures, and both nonoperative and operative therapies for NTOS. NTOS represents the most common subtype of thoracic outlet syndrome and can significantly impair quality of life. Botulinum toxin injection into the anterior scalene muscle, or even the middle scalene or pectoralis minor muscles, can reduce the symptoms of this syndrome. The best available evidence for botulinum toxin therapy to the cervicothoracic muscles supports the value of this treatment for reducing pain in the affected extremity, and for an approximate duration of 2 months or more. Surgical approaches and newer minimally invasive surgical approaches offer high rates of improvement in select centers.Keywords: thoracic outlet syndrome, neurogenic thoracic outlet syndrome, anterior scalene muscle, brachial plexus, compression neuropathy